Managing intellectual property in inter-firm R&D collaborations in knowledge-intensive industries. (23rd January 2008) - Bader, Martin A.
Managing intellectual property plays a crucial role in a collaborative innovation environment by providing legal protection, especially when supporting factual protection strategies that enable profits from temporary monopolies. However, legal protection strategies are a novelty in emerging business fields, such as the knowledge-intensive industry sector, as innovation and value creation are shifting towards service innovations that are difficult to tackle by legal protection instruments. The ways in which intellectual property can be managed in such an environment is, therefore, the subject of this research that follows a multiple-case design. Four dominant patterns get identified, discussed and summarised with respect to the collaborative knowledge-intensive industry environment: (1) multiplicator, (2) leverager, (3) absorber, (4) filtrator.